Alteraciones del sistema antioxidante en retinopatía diabética - Patricia, Hernández-Rodríguez (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2004)
The diabetic with a deficient blood glucose control have an antioxidant activity total diminished, what causes defects in the protection against the free radicals of oxygen, specifically is altered the susceptibly al oxidative damage. The alteration of the glucose implies increase production of sorbitol and of glutation and may cause to damage in crystalline and retain, involving to a partial or total loss of the vision. Clinical trials diverse favor the hypothesis that the activity of the enzymes of the antioxidant system, are associates with microvascular damages in it retain, nevertheless, some authors have reported studies where there is not a statistically significant association, consequently, is important to present studies that permit to measure the antioxidant state total since this is a reflection of the free levels of radicals and of the ocular damage. With this article intends to carry out a revision on the role and the possible implication, to preventive level, that can have the association among alterations of the antioxidant system and the diabetic retinopathy; therefore would be able to determine, of indirect form, the start and the severity of the damage in retaining, which would permit to continue an early therapeutic conduct generating primary prevention.